Wybrane aspekty controllingu finansowego w bankach spółdzielczych w Polsce - Siudek, Tomasz (Chosen aspects of financial controlling in cooperative banks in Poland, 2006)
The article presents normative size of financial indicators in co-operative banks in Poland in between years 1995 and 2002. Reassessed values of financial indicators are able to be utilized in the analysis of the comparative financial standing of cooperative banks and in planning financial of their activity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 116-122